Dielectric spectroscopy of a composite of polyvinyl alcohol cyanoethyl ether with graphene-modified ferroelectric barium titanates - Вачаган Тигранович Аванесян; Максим Максимович Сычев; Андрей Геннадьевич Чекуряев (Physics of Complex Systems, 2021)
The paper presents the results of an experimental study of the dielectric properties of a composite with a polymer matrix based on polyvinyl alcohol cyanoethyl ether (CEPVA) with a filler—ferroelectric barium titanate BaTiO3 modified with graphene nanoparticles. The behavior of frequency dependences of the components with complex permittivity and electrical modulus indicates the relaxation character of the dielectric polarization with the participation of polar formations of the functional components of the composite under study.